Ras-ERK1/2 signalling promotes the development of osteosarcoma through regulation of H4K12ac through HAT1. Issue 1 (4th December 2019) - Zhang, Jingzhe; Liu, Meihan; Liu, Wanguo; Wang, Wenjun
Abstract: Histone H4 acetylation at lysine 12 (H4K12ac) has been reported to be associated with the poor prognosis of pancreatic cancer. The study intends to study whether H4K12ac participates in regulating the carcinogenic effect of Ras-ERK1/2 on osteosarcoma (OS). The plasmids of pEGFP-N1, pEGFP-Ras WT and pEGFP-K-Ras G12V/T35S were transfected into MG-63 cells, the protein levels of H4K12ac and ERK1/2 were analyzed by Western blot. Effects of H4K12ac on cell proliferation and migration of MG-63 cells were tested by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-2Htetrazolium bromide solution (MTT), transwell, soft-agar colony formation and flow cytometry assays. Effect of H4K12ac on the transcription of ERK1/2 downstream genes was analyzed by RT-qPCR and ChIP assays. The involvements of HDAT6, HAT1 and MDM2 in cell proliferation and migration of MG-63 cells were finally studied. We found that H4K12ac was specifically down-regulated by Ras-ERK1/2 activation in MG-63 cells. H4K12ac suppressed Ras-ERK1/2-induced cell viability, colony formation and migration in MG-63 cells. Additionally, HDAC6 silence recovered Ras-ERK1/2-repressed H4K12ac expression, as well as inhibited the carcinogenic effect of Ras-ERK1/2 on MG-63 cells. Besides, down-regulated H4K12ac induced by Ras-ERK1/2 was found to be associated with MDM2-mediated HAT1 degradation. In conclusion, these results testified that Ras-ERK1/2 signalling promoted the development of OS by mediating H4K12ac through MDM2-mediated HAT1 degradation.